Bullying and Its Associated Factors among School-Aged Adolescents in Thailand - Supa Pengpid; Karl Peltzer (The Scientific World Journal)
The aim of this study were to assess bullying and its associated factors in school-going adolescents in Thailand. Using data from the Thailand Global School-Based Student Health Survey (GSHS) 2008, the prevalence of being bullied and its associated factors among adolescents (N=2758) was assessed. The study found an overall prevalence of being bullied on one or more days during the past 30 days of 27.8%, 32.9% among males and 23.2% among females. The predominant forms of being bullied were among boys being hit, kicked, pushed, shoved around, or locked indoors and among girls making fun of with sexual jokes, comments, and gestures. Among boys risk factors for having been bullied were younger age (adjusted odds ratio to (AOR): 0.34; 95% confidence interval (CI): 0.18–0.65), having been in a physical fight (AOR: 3.64; 95% CI: 2.84–4.66), being physically inactive (AOR: 1.49; 95% CI: 1.04–2.15), truancy (AOR: 1.66; 95% CI: 1.13–2.45), and psychosocial distress (AOR: 2.07; 95% CI: 1.14–3.74), and among girls risk factors for having been bullied were having been in a physical fight (AOR: 2.91; 95% CI: 2.00–4.24), lack of parental bonding (AOR: 0.71; 95% CI: 0.51–0.99), and psychosocial distress (AOR: 2.37; 95% CI: 1.39–4.03). Results may inform school health programmes on the prevalence and correlates of bullying among adolescents in Thailand.